2010
DOI: 10.1128/iai.00118-10
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilisEnterotoxin Induces Human β-Defensin-2 Expression in Intestinal Epithelial Cells via a Mitogen-Activated Protein Kinase/IκB Kinase/NF-κB-Dependent Pathway

Abstract: Enterotoxigenic Bacteroides fragilis (ETBF) produces an approximately 20-kDa heat-labile enterotoxin (BFT) that plays an essential role in mucosal inflammation. Although spontaneous disappearance of ETBF infection is common, little information is available on regulated expression of antibacterial factors in response to BFT stimulation. This study investigates the role of BFT in human β-defensin 2 (hBD-2) induction from intestinal epithelial cells. Stimulation of HT-29 and Caco-2 intestinal epithelial cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 45 publications
3
59
0
3
Order By: Relevance
“…32 Purification of BFT and Cell Culture Conditions BFT was purified from the culture supernatant of a highly toxigenic ETBF strain as described previously. 10,[25][26][27][28][29][30]33 BFT preparation purity was confirmed by sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE). Typical preparations of BFT contained 0.5-1.2 mg protein/ml as measured by the BCA protein assay.…”
Section: Materials and Methods Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Purification of BFT and Cell Culture Conditions BFT was purified from the culture supernatant of a highly toxigenic ETBF strain as described previously. 10,[25][26][27][28][29][30]33 BFT preparation purity was confirmed by sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE). Typical preparations of BFT contained 0.5-1.2 mg protein/ml as measured by the BCA protein assay.…”
Section: Materials and Methods Reagentsmentioning
confidence: 99%
“…Moreover, there is no evidence of BFT-induced MAPKs or AP-1 activation leading to Lcn-2 expression, although those signaling molecules have been reported to be activated in intestinal epithelial cells exposed to BFT. 10,[25][26][27][28][29][30][31] In the studies reported here, we investigated the regulation of Lcn-2 expression in response to BFT stimulation, and found that stimulation with BFT upregulates Lcn-2 expression in intestinal epithelial cells through the activation of MAPKs and the AP-1 signaling pathway.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The mitogen-activated protein kinases (MAPKs) such as p38, JNK and ERK protein kinase are involved in the signaling cascades leading to hBD-2 expression upon various stimuli (Jang et al, 2004;Méndez-Samperio et al, 2007;Yoon et al, 2010). We observed that JNK inhibitor, but not ERK and p38 MAPK inhibitors, suppressed HIV-1 Tat-induced mRNA expression of hBD-2 as well as the production of hBD-2 ( Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have indicated that the activity of MAP kinases such as p38, JNK and ERK protein kinase is involved in hBD-2 expression upon various stimuli (Jang et al, 2004;Méndez-Samperio et al, 2007;Yoon et al, 2010). To further analyze the effect of the MAPK superfamily pathway on HIV-1 Tat-mediated hBD-2 production, we measured HIV-1 Tat-induced hBD-2 production in the presence of pathway-specific inhibitors.…”
Section: Hiv-1 Tat Induced Jnk Activation That Is Required For Hbd-2 mentioning
confidence: 99%